Contentious Rituals and Intergroup Relations: Parading in Northern Ireland - Rickard, Kit; Hollenweger, Giovanni; Weber, Sigrid; Bakke, Kristin (Cambridge University Press, 2025)
In some divided societies, identity-based groups engage in ‘contentious rituals’, such as public parades or commemorative events, to cultivate the group’s collective social memory and build solidarity. We examine whether and how such rituals perpetuate group divisions in post-conflict societies, drawing on evidence from a case study of parading in Northern Ireland. Every year, contentious parades in this post-conflict society have the potential to raise tensions between the two major communities, Catholics and Protestants. Using a mixed-methods design, we show that parades in Northern Ireland are detrimental to intergroup attitudes. Our research design relies on compiling geolocated data on over 55,000 parades (2002–22), analyses of both nationally representative longitudinal surveys (2003–19) and an original survey fielded in 2022, and insights from qualitative fieldwork conducted during the height of the parading season in 2023.
Keywords: 63 Sociología; ODS 16 - Paz, justicia e instituciones sólidas; rituals; Northern Ireland; post-conflict society; intergroup relations